Continuing trastuzumab therapy after surgical treatment of brain metastase – a case report - Kolenda, Piotr; Litwiniuk, Maria (Contemporary Oncology/Współczesna Onkologia, 2010)
Trastuzumab (Herceptin), a recombinant humanized monoclonal antibody, has proved efficiency in the treatment of the overexpressed HER2 metastatic breast cancer. Although it has been commonly applied for over 10 years, there are still many questions on its application without answers. The way one should treat patients with this antibody when a cancer progression appears is one of them. In a such situation one may either apply a trastuzumab free second-line chemotherapy or continue a trastuzumab-based therapy with a different cytostatic. The oral drug lapatinib is another treatment option, an inhibitor directed against the epidermal growth factor receptor and the intracellular HER 2 receptor domain. An interesting case of a patient with the overexpressed HER 2 breast cancer has been presented in this work. Trastuzumab-based therapy has been applied to the patient because of the recurrence of the disease and it resulted in a 35-month complete remission of the disease. Then a single metastasis to the brain has been diagnosed with no metastases to other body organs (computed tomography, magnetic resonance and positron emission tomography (PET) confirmed the test results). The patient had a radical surgery and the histopathological examination of the surgical specimen showed metastatic character. Having stated no serious side effects, the treatment with trastuzumab is being continued up to now. After 40 months of the treatment a total remission of the disease continues. In total, the overall survival time for the patient under trastuzumab therapy is 76 months.